2000
DOI: 10.1016/s0003-4878(99)00116-7
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos exposure and laryngeal cancer

Abstract: Objective: To carry out a systematic review of the evidence relating asbestos exposure to the risk of laryngeal cancer. Method: All identi®ed studies of asbestos workers providing data on laryngeal disease were reviewed, together with studies of laryngeal cancers giving epidemiological or experimental evidence of associated exposures. Results: Confounding due to smoking and alcohol intake, and to a lesser extent diet and socioeconomic factors, creates a major diculty over the identi®cation of any asbestos or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 36 publications
0
21
0
2
Order By: Relevance
“…Laryngeal cancer and asbestos exposure has been evaluated in some studies. Several studies including a cohort of Quebec chrysotile workers found no association between laryngeal carcinoma and asbestos exposure (25)(26)(27)(28)(29)(30)(31)(32). In a review it was concluded that neither the longitudinal or cross-sectional data could support asbestos as an etiologic factor for laryngeal cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Laryngeal cancer and asbestos exposure has been evaluated in some studies. Several studies including a cohort of Quebec chrysotile workers found no association between laryngeal carcinoma and asbestos exposure (25)(26)(27)(28)(29)(30)(31)(32). In a review it was concluded that neither the longitudinal or cross-sectional data could support asbestos as an etiologic factor for laryngeal cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…-Asbestos and occupational exposure: There is controversy regarding occupational asbestos exposure and increased risk for developing laryngeal SCC (80). However, there is evidence supporting other occupational exposures and increased risk of laryngeal SCC, such as polycyclic aromatic hydrocarbons, metal dust, cement dust, varnish, lacquer, etc.…”
Section: Etiology -Tobacco and Alcoholmentioning
confidence: 99%
“…Asbestos inhalation causes mesothelioma and lung cancer; however, its role in laryngeal cancers is uncertain (8)(9)(10)(11). Animal models are lacking, and epidemiologic evidence is inconsistent.…”
Section: Asbestosmentioning
confidence: 99%
“…Occupational exposure to mists of strong inorganic acids is an established cause of laryngeal cancer (3). Other suspected risk factors for laryngeal cancer include work in the rubber industry (4,5) and exposure to cement dust (6,7) and asbestos (8)(9)(10)(11). There is little evidence of a relationship between occupational exposures and cancers of the oral cavity and pharynx; some chemicals that have been linked to these cancers include polycyclic aromatic hydrocarbons (12) and formaldehyde (13).…”
mentioning
confidence: 99%